TOKOH DALAM NAMA-NAMA JALUR DI KUANTANSINGINGI - Raja Saleh (Balai Bahasa Provinsi Riau, 2013)
The problem in this research is how the naming system of long boat in Kuantansingingi is. The research, entitled